Thyroid and endostyle development in cyclostomes provides new insights into the evolutionary history of vertebrates - Wataru Takagi; Fumiaki Sugahara; Shinnosuke Higuchi; Rie Kusakabe; Juan Pascual-Anaya; Iori Sato; Yasuhiro Oisi; Nobuhiro Ogawa; Hiroshi Miyanishi; Noritaka Adachi; Susumu Hyodo; Shigeru Kuratani (BMC Biology, 2022)
Abstract Background The endostyle is an epithelial exocrine gland found in non-vertebrate chordates (amphioxi and tunicates) and the larvae of modern lampreys. It is generally considered to be an evolutionary precursor of the thyroid gland of vertebrates. Transformation of the endostyle into the thyroid gland during the metamorphosis of lampreys is thus deemed to be a recapitulation of a past event in vertebrate evolution. In 1906, Stockard reported that the thyroid gland in hagfish, the sister cyclostome group of lampreys, develops through an endostyle-like primordium, strongly supporting the plesiomorphy of the lamprey endostyle. However, the findings in hagfish thyroid development were solely based on this single study, and these have not been confirmed by modern molecular, genetic, and morphological data pertaining to hagfish thyroid development over the last century. Results Here, we showed that the thyroid gland of hagfish undergoes direct development from the ventrorostral pharyngeal endoderm, where the previously described endostyle-like primordium was not found. The developmental pattern of the hagfish thyroid, including histological features and regulatory gene expression profiles, closely resembles that found in modern jawed vertebrates (gnathostomes). Meanwhile, as opposed to gnathostomes but similar to non-vertebrate chordates, lamprey and hagfish share a broad expression domain of Nkx2-1/2-4, a key regulatory gene, in the pharyngeal epithelium during early developmental stages. Conclusions Based on the direct development of the thyroid gland both in hagfish and gnathostomes, and the shared expression profile of thyroid-related transcription factors in the cyclostomes, we challenge the plesiomorphic status of the lamprey endostyle and propose an alternative hypothesis where the lamprey endostyle could be obtained secondarily in crown lampreys.